Fabrication of Highly Stable Glyco‐Gold Nanoparticles and Development of a Glyco‐Gold Nanoparticle‐Based Oriented Immobilized Antibody Microarray for Lectin (GOAL) Assay. Issue 10 (8th January 2015) - Huang, Li‐De; Adak, Avijit K.; Yu, Ching‐Ching; Hsiao, Wei‐Chen; Lin, Hong‐Jyune; Chen, Mu‐Lin; Lin, Chun‐Cheng
Abstract: The design of high‐affinity lectin ligands is critical for enhancing the inherently weak binding affinities of monomeric carbohydrates to their binding proteins. Glyco‐gold nanoparticles (glyco‐AuNPs) are promising multivalent glycan displays that can confer significantly improved functional affinity of glyco‐AuNPs to proteins. Here, AuNPs are functionalized with several different carbohydrates to profile lectin affinities. We demonstrate that AuNPs functionalized with mixed thiolated ligands comprising glycan (70 mol %) and an amphiphilic linker (30 mol %) provide long‐term stability in solutions containing high concentrations of salts and proteins, with no evidence of nonspecific protein adsorption. These highly stable glyco‐AuNPs enable the detection of model plant lectins such as Concanavalin A, wheat germ agglutinin, and Ricinus communis Agglutinin 120, at subnanomolar and low picomolar levels through UV/Vis spectrophotometry and dynamic light scattering, respectively. Moreover, we develop in situ glyco‐AuNPs‐based agglutination on an oriented immobilized antibody microarray, which permits highly sensitive lectin sensing with the naked eye. In addition, this microarray is capable of detecting lectins presented individually, in other environmental settings, or in a mixture of samples. These results indicate that glyconanoparticles represent a versatile and highly sensitive method for detecting and probing the binding of glycan to proteins, with significant implications for the construction of a variety of platforms for the development of glyconanoparticle‐based biosensors. Abstract : Going for GOAL : A sensitive method for detecting lectins is constructed through in situ agglutination of glyco‐gold nanoparticles on an oriented immobilized antibody microarray surface that has been derivatized with high‐affinity boronic acid ligands (see figure).